2012
DOI: 10.1186/1757-2215-5-23
|View full text |Cite
|
Sign up to set email alerts
|

Serial measurements of serum PDGF-AA, PDGF-BB, FGF2, and VEGF in multiresistant ovarian cancer patients treated with bevacizumab

Abstract: IntroductionAnti-VEGF treatment has proven effective in recurrent ovarian cancer. However, the identification of the patients most likely to respond is still pending. It is well known that the angiogenesis is regulated by several other pro-angiogenic proteins, e.g. the platelet - derived growth factor (PDGF) system and the fibroblast growth factor (FGF) system. These other signaling pathways may remain active or become upregulated during anti-VEGF treatment.The aim of the present study was to investigate if po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Emerging evidence suggests that the PDGF system plays an essential role in ovarian cancer progression [22]. Still, there are only few published studies on PDGF-B expression in ovarian malignancies [23,24]. Our results confirmed that in women with ovarian cancer the sources of PDGF-B could be both tumor cells and endothelial cell/pericytes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Emerging evidence suggests that the PDGF system plays an essential role in ovarian cancer progression [22]. Still, there are only few published studies on PDGF-B expression in ovarian malignancies [23,24]. Our results confirmed that in women with ovarian cancer the sources of PDGF-B could be both tumor cells and endothelial cell/pericytes.…”
Section: Discussionsupporting
confidence: 81%
“…However, in stromal cells 40% of their cases stained positive for PDGFR-α. In another study from the same group Madsen et al [24] have measured serum PDGF-AA, PDGF-BB, FGF2, and VEGF concentrations in bevacizumab treated multiresistant ovarian cancer patients. The levels of these cytokines were up-regulated in ovarian cancer and were associated with stage and residual disease.…”
Section: Discussionmentioning
confidence: 99%
“…Many novel VEGF/VEGFR-targeted inhibitors have been reported to improve the prognosis and survival of patients more than chemotherapy alone does 42 , such as bevacizumab and ramucirumab [43][44][45] . However, when VEGF signaling is blocked, other compensatory angiogenic signaling pathways can regulate tumor angiogenesis, including the PDGF, FGF, and hepatocyte growth factor/Met signaling pathways 46 . Consequently, multi-agent therapy appears to be the optimal strategy for targeting angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggested that GRO-1 and sE-selectin may have an impact on the prognosis of CSCC patients by affecting FIGO stage or lymph node metastasis, thus GRO-1 and sE-selectin were not independent prognostic risk factors. Madsen et al (44) failed to verify the prognostic value of PDGF-AA in ovarian cancer. However, another study indicated the adverse prognosis of PDGF-AA in pancreatic cancer (26), thus the prognostic value of PDGF-AA in CSCC requires further investigation.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%